Sining biswal a video documentary on the American colonial and contemporary traditions in Philippine visual arts - Guillermo, Alice; Rivera, Alan A.; Sulicipan, Leila C. (Tuklas sining series, 1996)
A discussion of the work of classicists who were dominant for the first three decades of the century and then on to a description of the various styles of modernism. It also describes the various styles evolved in the last four decades from abstract expressionism to folk and naive painting to magic realism and social realism.